Hydrogel Spacer Rectal Wall Infiltration Associated With Severe Rectal Injury and Related Complications After Dose Intensified Prostate Cancer Stereotactic Ablative Radiation Therapy - McLaughlin, Mark F. (Adv Radiat Oncol, 2021)
The risk of rectal toxicity during and after prostate cancer radiation therapy is common to all treatment regimens. Hydrogel rectal spacers are increasingly being used to mitigate this risk and to facilitate dose-escalation, but also may infiltrate the rectal wall, with unclear clinical implication. We present a case of significant infiltration associated with severe late rectal injury (grade 4) and further grade 3 to 4 sequelae (recto-urethral fistula and associated osteomyelitis requiring exenteration) after high-dose stereotactic body radiation therapy for localized prostate cancer. The injury's temporal pattern associated with the expected timing of gel dissolution and displacement of infiltrated rectal layers potentially toward high dose regions together suggest a contributing role of the infiltration to the injury. In light of the rapid increase of hydrogel rectal spacer utilization, we review the case's evolution, concerning imaging findings, and associated literature and make suggestions regarding treatment planning and endoscopic assessment in the setting of infiltration or expected injury.